Peptidome profiling of venom from the social wasp Polybia paulista - Dias, Nathalia Batista [UNESP]; Souza, Bibiana Monson de [UNESP]; Gomes, Paulo Cesar [UNESP]; Brigatte, Patricia [UNESP]; Palma, Mario Sergio [UNESP] (Elsevier B. V., 2015)
Most crude venom from Polybiapaulista is composed of short, linear peptides; however, only five of these peptides are structurally and functionally characterized. Therefore, the peptides in this venom were profiled using an HPLC-IT-TOF/MS and MS(n) system. The presence of type -d and -w ions that are generated from the fragmentation of the side chains was used to resolve I/L ambiguity. The distinction between K and Q residues was achieved through esterification of the α- and ε-amino groups in the peptide chains, followed by mass spectrometry analysis. Fourteen major peptides were detected in P. paulista venom and sequenced; all the peptides were synthesized on solid-phase and submitted to a series of bioassays. Five of them had been previously characterized, and nine were novel toxins. The novel peptides correspond to two wasp kinins, two chemotactic components, three mastoparans, and two peptides of unknown function. The seven novel peptides with identified functions appear to act synergistically with the previously known ones, constituting three well-known families of peptide toxins (wasp kinins, chemotactic peptides, and mastoparans) in the venom of social wasps. These multifunctional toxins can cause pain, oedema formation, haemolysis, chemotaxis of PMNLs, and mast cell degranulation in victims who are stung by wasps.
Keywords: Esi-it-tof/ms; Peptidomics; Polycationic peptides; Rp-hplc; Wasp venom